2008
DOI: 10.1074/jbc.m804006200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Structure and Minimal Functional Unit of the Electrogenic Sodium Bicarbonate Cotransporter NBCe1-A

Abstract: The electrogenic sodium bicarbonate cotransporter NBCe1-A mediates the basolateral absorption of sodium and bicarbonate in the proximal tubule. In this study the oligomeric state and minimal functional unit of NBCe1-A were investigated. Wildtype (wt) NBCe1-A isolated from mouse kidney or heterologously expressed in HEK293 cells was predominantly in a dimeric state as was shown using fluorescence energy transfer, pulldown, immunoprecipitation, cross-linking experiments, and nondenaturing perfluorooctanoate-PAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 82 publications
6
69
0
1
Order By: Relevance
“…Together, these data suggest that NBCe1A form dimers and that the NH 2 termini from the two monomers are in close proximity, and likely pair up, to form a functional unit. A similar result was reported in another study measuring FRET when NBCe1A was tagged on the NH 2 terminus with EYFP or Cerulean and expressed in HEK293 cells (23). However, the fluorescent tags were not fused onto the COOH terminus of NBCe1A in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Together, these data suggest that NBCe1A form dimers and that the NH 2 termini from the two monomers are in close proximity, and likely pair up, to form a functional unit. A similar result was reported in another study measuring FRET when NBCe1A was tagged on the NH 2 terminus with EYFP or Cerulean and expressed in HEK293 cells (23). However, the fluorescent tags were not fused onto the COOH terminus of NBCe1A in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Together these data suggest that the NBCe1 exists in a dimeric form. Similar findings were reported where membrane fractions were isolated from mouse renal cortex or HEK293 cells expressing NBCe1A and analyzed by PAGE using mild solubilization in the nondissociative detergent perfluoro-octanoic acid (PFO) (23).This study found that the dimeric form was the most dominant oligomer, but a minor tetramer coexisted with nondenaturing conditions (i.e., no DTT). Biochemical studies of the AE1 (SLC4A1) oligomeric structure have indicated that the AE1 protein forms dimers and tetramers with similar nondenaturing conditions (3,4,22).…”
Section: Discussionsupporting
confidence: 79%
“…These variants differ in their Nand C-terminal regions but have the identical transmembrane region (8). NBCe1-A exists as a homodimer in the plasma membrane with each monomer functioning independently (10). Each monomer consists of an N-terminal cytoplasmic region, a C-terminal transmembrane region, and a short C-terminal cytoplasmic tail.…”
Section: ϫmentioning
confidence: 99%
“…The transporter exists as a homodimer with each monomer functioning independently (18). Each NBCe1-A monomer consists of 1,035 amino acids with both of the NH 2 and COOH termini located in the cytosol.…”
mentioning
confidence: 99%